REALITAS KOMUNIKASI MAHASISWA PENDATANG DENGAN MAHASISWA LOKAL DI BANDUNG - Dudi Yudhakusuma (Prodi Ilmu Komunikasi FISIP Universitas Langlangbuana, 2016)
The existence of immigrant students causing cultural contact can not be avoided between groups of immigrant students with local students and surrounding communities. This study focuses on the reality of intercultural communication between immigrant students and local students in a campus environment at Communication Studies departement University of Langlangbuana Bandung. This study examines the mechanisms of interaction of immigrant students and local as well as the extent of their knowledge in carrying out social interaction within the community of Sunda, especially in the social environment of the campus, as well as obstacles that constraint. Using qualitative research methods through a phenomenological perspective. Technique data analysis was done descriptively by collecting data through interviews, observation through participation, and documentation. The information obtained from informants not only alone but also of the events and situations that are observed in this study. Interactions mechanism authors have described, divided into two or pattern of intra and inter-ethnic context. Their perception of Bandung and campus UNLA started slowly but surely changes in accordance with the interaction they are doing. Based on the results of the study authors make a typology of immigrant students are Egalitarian, Moderate, and Conservative. Barriers that occur can be derived from internal and external factors students themselves.